2018
DOI: 10.1111/epi.14067
|View full text |Cite
|
Sign up to set email alerts
|

Ictal connectivity in childhood absence epilepsy: Associations with outcome

Abstract: Pretreatment ictal connectivity differences in children with CAE were associated with response to antiepileptic treatment. This is a possible mechanism for the variable treatment response seen in patients sharing the same epilepsy syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 43 publications
7
39
0
Order By: Relevance
“…The connectivity networks and sources during the evolvement of SWDs with spatial and temporal profiles were described (30). Tenney et al revealed that different ictal connectivities in pretreatment were related with response to antiepileptic treatment (31). And the changes of the effective connectivity (EC) network in specific frequency during interictal period were reported by Wu et al (32).…”
Section: Introductionmentioning
confidence: 99%
“…The connectivity networks and sources during the evolvement of SWDs with spatial and temporal profiles were described (30). Tenney et al revealed that different ictal connectivities in pretreatment were related with response to antiepileptic treatment (31). And the changes of the effective connectivity (EC) network in specific frequency during interictal period were reported by Wu et al (32).…”
Section: Introductionmentioning
confidence: 99%
“…Direct applications are most apparent in surgical epilepsies where network approaches have already demonstrated utility in identifying the epileptogenic region for resection and predicting postoperative outcomes of both seizure freedom and functional deficits . Pertaining to the nonsurgical childhood epilepsies, an understanding of network effects has the potential to yield new biomarkers including, as already demonstrated in one study, the possibility of predicting medication refractoriness . In addition, as neuromodulation becomes increasingly viable, this knowledge will provide the requisite background for targeted network modulation, which could lead to improved cognitive outcomes in affected children.…”
Section: Discussionmentioning
confidence: 99%
“…91 Pertaining to the nonsurgical childhood epilepsies, an understanding of network effects has the potential to yield new biomarkers including, as already demonstrated in one study, the possibility of predicting medication refractoriness. 74 In addition, as neuromodulation becomes increasingly viable, this knowledge will provide the requisite background for targeted network modulation, which could lead to improved cognitive outcomes in affected children. A proof of concept has already been demonstrated using transcranial magnetic stimulation to strengthen the attention network and improve cognitive task performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations